New K–AR ages of tchabal mbabo alkaline volcano massif, Cameroon volcanic line and adamawa plateau (central Africa) - Aminatou, Fagny Mefire; Oumarou Faarouk, Nkouandou; Robert, Temdjim; Jacques-Marie, Bardintzeff; Herve, Guillou; Dan, Stumbea; Abdelhak, Boutaleb (International Journal of Advanced Geosciences, 2016)
Tchabal Mbabo in Central Africa is a voluminous volcano massif composed of alkali lava series. K-Ar geochronology data obtained from three samples of basanite - trachyandesite composition defined at least two volcanic activities. The first at end Eocene (38.22 ± 0.80 Ma) and the second during Oligocene (28.88 ± 0.61 and 28.60 ± 0.60Ma). The distribution of different ages along the Cameroon Volcanic Line is difficult to council with any migration of magmatic activity, as previously suggested. The most realistic scenario for the formation of Cameroon Line is that the ascent of lavas has been favored by the crustal discontinuities inherited from the Pan-African orogeny and reactivated during Mesozoic and Cenozoic. ICP MS and ICP AES analyses show that basanite lavas are the result of 2 % melting of sub-lithospheric mantle source containing garnet and phlogopite phases; the trachyandesites are formed by fractional crystallization of K-feldspar, amphibole, clinopyroxene and Fe-Ti oxides.